2006
DOI: 10.1007/s11270-005-9073-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Biomass and Tolerance of Microbial Community on an Aged Heavy Metal Polluted Floodplain in Japan

Abstract: The objective of the present study was to increase understanding of the effects of heavy metal pollution and soil properties on microorganisms in relation to the biomass and microbial functional community. Soil samples were collected from aged polluted and reference sites on a floodplain. The soil Cu, Zn and Pb total concentrations were much higher at the polluted sites (average 231.6-309.9 mg kg −1 , 195.7-233.0 mg kg −1 , and 72.4-86.0 mg kg −1 , respectively) than at the reference site (average 33.3-44.0 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…In several instances, strongest correlations were indicated with total metal concentrations, rather than with the more bioavailable pore water metal fractions. This result in Lake DePue sediments was similar to the result that Kamitani et al (2006) reported for historically contaminated floodplain soils, where soils with higher total Cu, Zn and Pb showed lower functional diversity and higher Cu stress tolerance than control soils, even though more labile metal fractions showed similar concentrations between their four sites. These results highlight the complex nature of microbial community adaptation to long-term metal exposure, and suggest that further field-based studies of chronically exposed populations may be needed to elucidate the interactions between metal fractionation and population diversity.…”
Section: Discussionsupporting
confidence: 89%
“…In several instances, strongest correlations were indicated with total metal concentrations, rather than with the more bioavailable pore water metal fractions. This result in Lake DePue sediments was similar to the result that Kamitani et al (2006) reported for historically contaminated floodplain soils, where soils with higher total Cu, Zn and Pb showed lower functional diversity and higher Cu stress tolerance than control soils, even though more labile metal fractions showed similar concentrations between their four sites. These results highlight the complex nature of microbial community adaptation to long-term metal exposure, and suggest that further field-based studies of chronically exposed populations may be needed to elucidate the interactions between metal fractionation and population diversity.…”
Section: Discussionsupporting
confidence: 89%
“…The presence of the hyperaccumulator resulted in changes in the soil environment and decreases in bioavailable metals. However, some work has suggested that nutrient elements can obscure the effects of heavy metals on soil microbial characteristics [18,23], and other studies have reported that organic matter and nutrients in heavy metal contaminated soils can stimulate soil microorganisms, resulting in increases in their biomass and activity [2,16]. In the present study most soil nutrients (other than phosphorous in planted soils) showed lower concentrations compared with unplanted soils and any nutrient effect may have been weak compared to the effects of the heavy metals on microbial properties.…”
Section: Discussionmentioning
confidence: 99%
“…The main focus of research in the past has been the detrimental effects of heavy metals added to soils through the use of sewage sludge for crop production (Chander & Brookes, 1991;Fließbach, Martens, & Reber, 1994), while less attention has been given to other sources of heavy metals (Dai et al, 2004;Kamitani, Oba, & Kaneko, 2006). In Germany, exhaust dust from lead factories is an important source of heavy metal contamination (Chander, Dyckmans, Hoeper, Joergensen, & Raubuch, 2001a;Chander, Dyckmans, Joergensen, Meyer, & Raubuch, 2001b).…”
Section: Introductionmentioning
confidence: 99%